Obsolescencia de propiedad, planta y equipos en ganadería de la Cooperativa de Producción y Comercialización La Clementina - Ramirez Arguello, Yovely Amparo (2020)
Production and Marketing Cooperative “La Clementina” Workers-Owners is located in La Unión Rural Parish, Babahoyo Canton, Los Ríos Province, it is one of the largest companies and recognized for its agriculture dedicated to three economic activities: Agricultural, Livestock and Commissariat, the livestock activity is the object of study for the development of this work for the reason that it presents in its accounting records in the XASS system 12 fixed assets in a state of obsolescence that in the operation are not being used and have not been given proper treatment of said assets, these assets are not generating income for the company, which is why analyzes are carried out through financial ratios, this being the rotation of fixed assets to verify how it affects having those assets that are no longer in use in the development of activities, reflecting a variation in the calculation of the ratios that is significant in comparison with the indicator established in the market in the livestock branch, that is why the company must proceed to carry out a treatment of those obsolete assets proceeding to withdraw the assets from the plant, for this two options are presented: they are exchanged for another with the same characteristics or another with different characteristics, registering a charge or credit obtained in that action, due to the influence of the state in which the asset is located and the years that it has already been operating in the organization.